Kenaikan Omzet UMKM Makanan dan Minuman di Kota Bogor Pasca Sertifikasi Halal - Hana Khairunnisa; Deni Lubis; Qoriatul Hasanah (Department of Islamic Economics, IPB University, 2020)
Halal certification is one of the company’s strategy that aims to retain their consumers and become a difference with competitors and to give added value for product. Most of the researchers have proved that halal certificates affect big companies’ total revenue. However, there are not many studies that have proved that halal certificate would affect the total revenue of micro, small, and medium enterprises (MSMEs), especially in Bogor City. This research aims to determine the characteristics of MSMEs’ owners and their business, analyze the changes of MSME’s total revenue before and after owning a halal certificate, and the factors that affect MSMEs’ total revenue after owning a halal certificate. The questionnaire data were collected through an interview with 40 food and beverage MSMEs’ owners who have halal certificates in Bogor City. This research uses descriptive analysis, paired sample t-test, and multiple linear regression analysis as the analysis methods. Results based on this research showed that there was a difference in the total revenue of MSMEs before and after owning a halal certificate. The factors that have positive and significant effects of MSMEs’ total revenue influences are capital, work hours, length of business, and a dummy of promotion.